2012
DOI: 10.1021/jf303560f
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability of Dispersions Prepared from Purified Marine Phospholipid and the Role of α-Tocopherol

Abstract: The objective of this study was to investigate the oxidative stability of dispersions prepared from different levels of purified marine phospholipid (PL) obtained by acetone precipitation, with particular focus on the interaction between α-tocopherol and PL in dispersions. This also included the investigation of nonenzymatic browning in purified marine PL dispersions. Dispersions were prepared by high-pressure homogenizer. The oxidative and hydrolytic stabilities of dispersions were investigated by determinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 26 publications
5
24
0
Order By: Relevance
“…This was also perceived in a previous work [17] although the authors did not expose any explanation for this behavior. This behavior was unexpected since, in unilamellar liposomes, a higher content of the lipid phase leads to the formation of larger liposomes, which results in an increased interfacial area [18], and this should favor the oxidation in higher lipid content liposomal suspensions.…”
Section: ____________________________________________________________supporting
confidence: 49%
“…This was also perceived in a previous work [17] although the authors did not expose any explanation for this behavior. This behavior was unexpected since, in unilamellar liposomes, a higher content of the lipid phase leads to the formation of larger liposomes, which results in an increased interfacial area [18], and this should favor the oxidation in higher lipid content liposomal suspensions.…”
Section: ____________________________________________________________supporting
confidence: 49%
“…In a marine phospholipid liposome system, Maillard reaction in the presence of -tocopherol was again confirmed through measurement of Strecker aldehydes, color changes and pyrrole content and proved to suppress the formation of volatile lipid oxidation. 109 Shimajiri et al 110 reported antioxidant activity of amine-containing phospholipids (PC, PE and SPM) and further suggested that the presence of -tocopherol was essential to the reaction that produced antioxidative Maillard reaction products.…”
Section: Antioxidative Properties Of Phospholipid Maillard Reaction Pmentioning
confidence: 99%
“…In addition, the presence of significant amounts of PL and a-tocopherol together might be another reason for better oxidative stability of MGK than MPN [3,4]. In addition, our previous study also showed that stabilization of PL dispersions was due to the presence of a-tocopherol [36].…”
Section: Lipid Oxidation In Fortified Productsmentioning
confidence: 91%